Pengaturan Hukum Pada Persidangan In Absentia dalam Perkara Tindak Pidana Korupsi (Studi Putusan Nomor 65/Pid.Sus.Tpk/2016/PN.Bgl jucto Putusan Nomor 15/PLW/Pid.Sus/TPK/2016/PT.Bgl) - I Gusti Ayu Stefani Ratna Maharani (Fakultas Hukum, Universitas Warmadewa, 2025)
The aim of writing this article is to analyze the legal arrangements for in absentia conferences in corruption cases using a study of decision number 65/Pid.Sus.Tpk/2016/PN.Bgl jucto Decision Number 15/PLW/Pid.Sus/TPK/2016 /PT. Bgl. The writing method used in this paper is the normative legal writing method, namely legal research that uses an approach through documents or secondary data to be able to discuss the problem formulation in this journal. Regarding the results obtained in this writing, namely trial in absentia in cases of criminal acts of corruption as referred to in the current laws and regulations, based on the provisions of Article 38 in the PTPK Law, in principle it is carried out in two cases, namely in the event that the sender has been summoned personally. legal, and not present at the court hearing and to save state financial losses. The presence of a thief/suspect in the investigation process until the examination in court is a space for detectives who have the right to defend themselves, property rights, freedom and honor. Apart from that, by the presence of the defendant during the examination and conference, the defendant/suspect can clearly understand the charges presented to him as well as the information or other evidence addressed to him.